Ultrafine industrial aerosol as a risk factor for the health of smelting shop workers at a machine-building enterprise - Sharavara, L. P.; Dmytrukha, N. M.; Andrusyshyna, I. M.; Шаравара, Лариса Павлівна; Дмитруха, Н. М.; Андрусишина, І. М. (Запорізький державний медико-фармацевтичний університет, 2024)
Aim. To evaluate the amount and physicochemical properties of ultrafine industrial aerosol (UIA) in the work zone air (WZA) of smelting shop workers at a machine-building enterprise during various technological processes (melting, welding, and metal machining). Materials and methods. The physical properties of UIA particles were evaluated with NanoScan 3910 scanning spectrometer: the number of particles (number/cm3), particle surface volume (nm3/cm3), particle surface area (nm2/cm2), and nanoparticle mass concentration (μg/cm3) in the WZA of a furnace operator (n = 416), a welder (n = 315), a cutter (n = 286), a grinder (n = 78), and workers of the control group (n = 315). The chemical composition of the air samples was determined by inductively coupled plasma optical emission spectrometry (ICP-OES) using an Optima 2100 DV device. Results. It has been found that the highest concentration of UIA nanoparticles was recorded during metal melting at the workplaces (WP) of furnace operators (4.28 × 104 to 2.41 × 105 particles/cm3) and welders (3.01 × 104 to 3.34 × 105 particles/cm3). During mechanical metal processing, a much smaller number of nanoparticles was produced (for grinders, the number varied from 9.81 × 104 to 1.44 × 105 particles/cm3; for cutters, it varied from 2.71 × 104 to 1.94 × 105 particles/cm3). Indicators of surface area, surface volume and mass concentration at the WPs of furnace operators, welders, grinders and cutters exceeded the corresponding indicators of the control group for almost all sizes of suspended particles with statistically significant differences (p ≤ 0.05). It has been estimated that such metals as Al, Cu, Mg, Mo, Fe, and Ni were present in the workers’ WZA but their content did not exceed the current maximum permissible concentrations. Мета роботи – оцінити фізико-хімічні характеристики ультрадисперсного промислового аерозолю (УПА) повітря робочої зони (ПРЗ) працівників плавильного цеху машинобудівного підприємства. Матеріали і методи. Оцінили фізичні властивості частинок УПА за допомогою скануючого спектрометра NanoScan 3910: число частинок (кількість/см3), об’єм поверхні частинок (нм3/см3), площу поверхні частинок (нм2/см2) та масову концентрацію наночастинок (мкг/см3) у ПРЗ плавильника металу (n = 416), зварювальника (n = 315), обрубувача (n = 286), шліфувальника (n = 78) та працівників контрольної групи (n = 315). Хімічний склад проб повітря визначали методом оптико-емісійної спектрометрії з індуктивно зв’язаною плазмою (ОЕС-ІЗП) за допомогою приладу Орtima 2100 DV. Результати. Встановили, що найбільша кількісна концентрація наночастинок УПА зареєстрована під час плавлення металу на робочому місці (РМ) плавильника (4,28 × 104 до 2,41 × 105 частинок/см3) та зварювальника (3,01 × 104 до 3,34 × 105 частинок/см3). Під час механічної обробки металу утворюється значно менша кількість наночастинок (шліфувальник – від 9,81 × 104 до 1,44 × 105 частинок/см3, обрубувач – від 2,71 × 104 до 1,94 × 105 частинок/см3). Показники площі поверхні, об’єму поверхні та масової концентрації на РМ плавильника металу, зварювальника, шліфувальника та обрубувача перевищували відповідні показники в контрольній групі майже за всіма розмірами зважених частинок і мали статистично вірогідні відмінності (р ≤ 0,05). Визначили, що у ПРЗ працівників наявні метали: Al, Cu, Mg, Mo, Fe та Ni, – але їхній вміст не перевищував встановлених гранично припустимих концентрацій.
Ультрадисперсний промисловий аерозоль як фактор ризику для здоров’я працівників плавильного цеху машинобудівного підприємства
Sharavara L. P. - ORCID ID: 0000-0001-9102-3686
Keywords: nanoparticles; suspended particles of ultrafine aerosol; working environment; occupational exposure; workplace studies; наночастинки; зважені частинки ультрадисперсного аерозолю; робоче середовище; професійний вплив; дослідження на робочому місці